Analisis Broker Contract Kepengurusan Surat Izin Mengemudi dalam Islamic Framing (Studi Kasus Satpas Polres Demak) - Hadi Purnomo; Bayu Tri Cahya; Muhammad Lutfi Kuncoro; Suparwi Suparwi (Jurnal Ilmiah Ekonomi Islam, 2021)
Indonesia's bureaucratic administration is quite famous for its complexity. Starting from the procedures it is long and many of them, so the service that is less efficient in serving many people. Nowadays, until technology enters the modern era in driver’s licence management, services are still not optimal, because technology is only limited to being glanced at without being touched and considered to be improved to control service efficiency. Brokers are here to sneak in, offering convenience, speed to prospective driver’s licence applicants, so that transactions can be made between them. However, this incident made it unclear for the community. On the other hand, the actions of brokers are very helpful for driver’s licence applicants in their management. With the phenomenological qualitative methodology, it will be illustrated that the contract exists between the two parties (brokers and service users), because the clarity of a contract is the most important thing to tie cooperation between fellow social beings so that no one is harmed and is not partial. This research was conducted at the Demak Resort Police with a phenomenological approach and using interview data collection techniques, observation and documentation. The results of this study reveal that the contract that exists between the driver’s licence broker and service users in the management of the driver’s licence is the Ijarah Agreement. And this contract transaction is a legal thing. In general, the process of the driver’s licence management mechanism by brokers is haram. Because there is an element of risywah or bribery in the mechanism.